2Vita-B Physical: An Intelligent Home Rehabilitation System Based on Microsoft Azure Kinect - Antico, Mauro; Balletti, Nicoletta; Ciccotelli, Andrea; Ciccotelli, Marco; Laudato, Gennaro; Lazich, Aldo; Notarantonio, Marco; Oliveto, Rocco; Ricciardi, Stefano; Scalabrino, Simone; Simeone, Jonathan (Frontiers in Human Dynamics, 2021)
Active rehabilitation is an exercise-based program designed to improve the level of function of people with motor disabilities. The effectiveness of such programs is strongly influenced by the correctness of the exercise execution. An exercise done incorrectly could even lead to a worsening of the health status. For this reason, specialists are required to guide the patient during the execution of an exercise. The drastic reduction of the costs of motion tracking systems has paved the way to the implementation of virtual assistant software able to automatically assess the correctness of an exercise. In this paper 2Vita-B Physical is presented, a rehabilitation software system properly designed to support both (i) the patients, by guiding them in the correct execution of an exercise; and (ii) the physiotherapists, by allowing them to remotely check the progress of a patient. The motion capturing in 2Vita-B is performed by using the recently released Microsoft Kinect Azure DK. Thus, the system is easy to use and completely non-invasive. Besides the hardware and software requirements of the system, the results of a preliminary usability evaluation of the system conducted with 29 users is also reported. The results achieved are promising and provide evidence of the high usability of 2Vita-B Physical as home rehabilitation system.